Artificial Intelligence in Islamic Boarding School Management: A Conceptual Review on Governance, Educational Transformation, and Aqidah Preservation: Artificial Intelligence dalam Manajemen Pesantren: Tinjauan Konseptual tentang Tata Kelola, Transformasi Pendidikan, dan Penguatan Akidah - Kardina Engelina Siregar (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2024)
The rapid expansion of artificial intelligence (AI) in education has been widely discussed in global educational management literature; however, limited attention has been given to its application within Islamic boarding schools (pesantren), where educational governance is deeply intertwined with religious authority, traditional pedagogy, and the preservation of aqidah. This study aims to develop a conceptual synthesis that explains how AI-driven educational management can be aligned with the distinctive institutional characteristics of pesantren, rather than merely describing technological adoption. Employing an analytical literature review approach, this research systematically examines and synthesizes relevant studies published between 2019 and 2024 on AI in educational management, Islamic education, and Islamic ethical perspectives on technology. The findings identify four interrelated conceptual dimensions: managerial transformation through AI-enhanced administration, pedagogical shifts toward personalized learning, emerging ethical and aqidah-related tensions, and governance mechanisms that mediate technological innovation and religious values. Based on these dimensions, this study proposes an aqidah-oriented AI governance framework that emphasizes human-centered decision-making, ulama supervision, and alignment with maqasid al-shariah principles. The study contributes theoretically by integrating educational management theory with Islamic ethical governance in the context of AI, and practically by offering policy-relevant insights for pesantren leaders and policymakers seeking to balance technological innovation with the preservation of Islamic values in the digital era.